2018
DOI: 10.1002/app.46701
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive‐interpenetrating polymer network hydrogels for heavy metal ion recovery

Abstract: Thermoresponsive-interpenetrating polymer network (TR-IPN) hydrogels containing a large number of chelating groups were synthesized; the aim was to ensure the recovery of large amounts of heavy metal ions through temperature cycling across volume phase transition temperature of the hydrogel. The TR-IPN hydrogels were synthesized from poly(N-isopropylacrylamide) and alginate, and the ability of these hydrogels to adsorb a heavy metal ion, Cu(II), was investigated at different temperatures. In the experiment, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
1
Order By: Relevance
“…From the result, it is observed that although the Cu(II) recovery amount in our adsorbent is somewhat smaller than that of the adsorbent reported by Ochi, 43 the time required for Cu(II) adsorption is significantly shorter. In their case, the adsorbent used was thermoresponsive interpenetrating polymer network hydrogel type adsorbent consisting of alginate and PNIPAM.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…From the result, it is observed that although the Cu(II) recovery amount in our adsorbent is somewhat smaller than that of the adsorbent reported by Ochi, 43 the time required for Cu(II) adsorption is significantly shorter. In their case, the adsorbent used was thermoresponsive interpenetrating polymer network hydrogel type adsorbent consisting of alginate and PNIPAM.…”
Section: Resultscontrasting
confidence: 54%
“…Then, the amount of Cu(II) recovery is plotted against the time required for adsorption (Figure 11). In the same figure, the results of other researchers were also plotted for comparison 5,43,44 . It should be noted here that although their adsorbent also consisted of thermoresponsive polymer, their forms were in gel.…”
Section: Resultsmentioning
confidence: 96%
“…48 Considering the excessive consumption of nonrenewable resources and severe environmental pollution, the exploration of hydrogels from renewable resources has drawn significant attention. In recent years, as natural hydrophilic polymers, polysaccharides, including sodium alginate, [49][50][51] carboxymethyl cellulose, 52 chitosan, 53 starch 54 and carrageenan, [55][56] have been widely utilized as starting materials for fabricating hydrogels due to their non-toxicity, biocompatibility, biodegradability, and renewability. [57][58][59] Sodium alginate is a natural polymer with multiple carboxyl groups, which have outstanding coordination capability with divalent or polyvalent metal cations, 60 and is a suitable material for preparing SMHs and intelligent hydrogels.…”
Section: Introductionmentioning
confidence: 99%